Stem Cells: A Historical Review about Biological, Religious, and Ethical Issues - Ioannis Alexandros Charitos; Andrea Ballini; Stefania Cantore; Mariarosaria Boccellino; Marina Di Domenico; Elisa Borsani; Riccardo Nocini; Michele Di Cosola; Luigi Santacroce; Lucrezia Bottalico (Stem Cells International)
Stem cells can be used to replace damaged cells or regenerate organs and have broadened our knowledge of the development and progression of certain diseases. Despite significant advances in understanding stem cell biology, several problems limit their use. These problems are related not only to the growth of tumors in animal models and their rejection in transplant cases but also to ethical and social issues about the use of embryonic cells. The ethical-scientific debate on this type of cells has taken on great interest both for their application in regenerative medicine and for the potential possibilities in the field of cell and gene therapy. Different points of view often have the expression of a perception that depends on scientific goals or opportunities or on religious traditions and beliefs. Therefore, as the questions and doubts about when life begins, so do the answers for the use of these cells as therapy or otherwise. So, in addition to the origin of stem cells, there are currently some social bioethical (such as political and legislative issues) and religious dilemmas. The purpose of the study is aimed at being a narrative on the history of stem cells and the evolution of their use to date, as well as to clarify the bioethical position of the various religions today in comparison with the social ones regarding the research and use of embryonic and adult ones. Hence, their biological hypostasis regarding the concepts of “conception” and “fertilization” and their development and therapeutic use compared to those of the main theological doctrines.